Enteric Parasitic Infection Among Antiretroviral Therapy Naïve HIV-Seropositive People: Infection Begets Infection-Experience from Eastern India - Mitra, Suman (J Glob Infect Dis, 2016)
CONTEXT: Parasitic opportunistic infections (POIs) frequently occur in HIV/AIDS patients and affect the quality of life. AIMS: This study assessing the standard organisms in the stool of HIV-positive patients, their comparison with HIV-negative controls, their relation with various factors, is the first of its kind in the eastern part of India. SETTINGS AND DESIGN: hospital-based case–control study. MATERIALS AND METHODS: A total of 194 antiretroviral therapy naïve HIV-positive patients (18-60 years) were taken as cases and 98 age- and sex-matched HIV-negative family members as controls. Demographical, clinical, biochemical, and microbiological parameters were studied. STATISTICAL ANALYSIS USED: Odds ratio, 95% confidence interval, and P (< 0.05 is to be significant) were calculated using Epi Info 7 software. RESULTS: POI was significantly higher among HIV-seropositive cases (61.86%) (P < 0.001). Cryptosporidium was the most common POI in HIV-seropositive patients overall and without diarrhea; Entameba was the most common POI in patients with acute diarrhea, and Isospora was the most common POI in the patients having chronic diarrhea. Entameba was the most common POI in CD4 count <350 cells/μl while for CD4 count >350 cells/μl Cryptosporidium was the most common POI. Mean CD4 count was significantly (P < 0.001) lower among people having multiple infections. Male sex, hemoglobin <10 g/dl, WHO Clinical Stage 3 or 4, tuberculosis, absolute eosinophil count of more than 540/dl, CD4 count <350 cells/μl, and seroconcordance of spouses were significantly associated with HIV-seropositive cases having POI (P < 0.05). CONCLUSIONS: Physicians should advise HIV-infected patients to undergo routine evaluation for POI, and provision of chemoprophylaxis should be made in appropriate settings.